BOARD GAME SEBAGAI MEDIA UNTUK MEMBANGUN KARAKTER KEMANDIRIAN ANAK USIA 4-6 TAHUN - Nursyifani, Cahyaning Umul Chasanah (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2020)
One of the psychological developments that occur when the preschool child(4-6 years)is the emergence of a desire to take care of himself or called independent. In this modern age, Children often get facilities excess from parents so that children are less independent in solving a problem. This condition is often found in Indonesia, especially in urban areas. Learning independence of children who have the potential to be developed in Indonesia is through the board game media. Meanwhile, the board game about developing of attitude for pre-school children is still rarely be found. The board game in Indonesia began to be favored by the community, but the level of enthusiasm of society is still lacking. The result of this research is to stimulate the development of pre-schooler self-reliance through board game media.Key Words: preschool, Independent, Boardgame